Talking Stick Method Toward Student Learning Activities in Islamic Cultural History Lessons - Yahdinil Firda Nadhirah; Istianah Alfisyah; Juhji Juhji (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The purpose of this article was to determine the application of the talking stick learning method, choose students' learning activities, and analyze the effect of the talking stick learning method on students' learning activities in the history of Islamic culture at MTs Negeri 3 Cilegon. This research uses a quantitative approach and a quasi-experimental type of research with a non-equivalent control group design. The population in this study was all VIII graders at MTsN 3 Cilegon City, which consisted of 6 classes with 192 people. The sampling technique used was the purposive sampling technique. The instrument used is an observation sheet. The results showed that the application of the talking stick learning method was carried out well, students' learning activities were higher, and the t-count was 74,823, which was greater than the t-table at a significant rate of 0.05, namely 2.042. Thus, the study results conclude that applying the talking stick learning method in the history of Islamic culture at MTsN 3 Cilegon City provides better outcomes for student learning activities.